The missing De Morgan's law - coq

Coq uses constructive logic, which means that if you try to fill out
De Morgan's laws, you'll end up missing 2.
Namely, you can't prove:
Theorem deMorgan_nand P Q (andPQ : ~(P /\ Q)) : P \/ Q.
Abort.
Theorem deMorgan_nall {A} (P : A -> Prop) (allPa : ~forall a, P a) : exists a, ~P a.
Abort.
This makes sense, because you've have to compute whether it was
the left or right item of the or, which you can't do in general.
Looking at
"Classical Mathematics for a Constructive World"
(https://arxiv.org/pdf/1008.1213.pdf)
has the definitions
Definition orW P Q := ~(~P /\ ~Q).
Definition exW {A} (P : A -> Prop) := ~forall a, ~P a.
similar to De Morgan's law. This suggests an alternative formulation.
Theorem deMorgan_nand P Q (andPQ : ~(P /\ Q)) : orW (~P) (~Q).
hnf; intros nnPQ; destruct nnPQ as [ nnP nnQ ].
apply nnP; clear nnP; hnf; intros p.
apply nnQ; clear nnQ; hnf; intros q.
apply (andPQ (conj p q)).
Qed.
Theorem deMorgan_nall {A} (P : A -> Prop) (allPa : ~forall a, P a) : exW (fun a => ~P a).
Abort.
But, it doesn't work with negating forall. In particular, it gets stuck on
trying to convert ~~P a into P a. So, despite in the nand case
converting ~~P into P, it doesn't seem to work with forall.
You can also show that there is some element of a that has
P a.
Similarly, you could try to show
Theorem deMorgan_nexn {A} (P : A -> Prop) (exPa : ~exists a, ~P a) : ~~forall a, P a.
Abort.
but that gets stuck in that once you have the argument a,
the conclusion is no longer False, so you can't use ~~P -> P.
So, if you can't prove deMorgan_nall, is there any theorem like it?
Or is ~forall a, P a already as simplified as it can get?
More generally, when the conclusion is False, that allows for using
the law of excluded middle (P \/ ~P). Is there any counterpart
to that that works when the proposition takes an argument, that is
P : A -> Prop instead of P : Prop ?

The principle you are looking for is known as double negation shift. It is not valid in intuitionistic logic in general. Despite looking fairly innocuous at first, as its conclusion is a doubly-negated formula, it is actually quite potent. Indeed, DNS is essentially what is needed in order to interpret the axiom of choice through the double-negation translation.
Edit by scubed:
So, that means I have to add an axiom to handle this case. Using the axiom,
Axiom deMorgan_allnn : forall {A} (P : A -> Prop) (allPa : forall a, ~~P a), ~~forall a, P a.
Theorem deMorgan_nall {A} (P : A -> Prop) (allPa : ~forall a, P a) : exW (fun a => ~P a).
hnf; intros ex1; apply deMorgan_allnn in ex1.
apply ex1; clear ex1; hnf; intros all2.
apply (allPa all2).
Qed.

Related

Understanding specialize tactic

Trying to comprehend the answer of #keep_learning I walked through this code step by step:
Inductive nostutter {X:Type} : list X -> Prop :=
| ns_nil : nostutter []
| ns_one : forall (x : X), nostutter [x]
| ns_cons: forall (x : X) (h : X) (t : list X), nostutter (h::t) -> x <> h -> nostutter (x::h::t).
Example test_nostutter_4: not (nostutter [3;1;1;4]).
Proof.
intro.
inversion_clear H.
inversion_clear H0.
unfold not in H2.
(* We are here *)
specialize (H2 eq_refl).
apply H2.
Qed.
Here is what we have before excuting specialize
H1 : 3 <> 1
H : nostutter [1; 4]
H2 : 1 = 1 -> False
============================
False
Here is eq Prop whose constructor eq_refl is used in specialize:
Inductive eq (A:Type) (x:A) : A -> Prop :=
eq_refl : x = x :>A
where "x = y :> A" := (#eq A x y) : type_scope.
I can't explain, how this command works:
specialize (H2 eq_refl).
I read about specialize in reference manual, but the explanation there is too broad. As far as I understand it sees that "1 = 1" expression in H2 satisfies eq_refl constructor and therefore eq proposition is True. Then it simplifies the expression:
True -> False => False
And we get
H1 : 3 <> 1
H : nostutter [1; 4]
H2 : False
============================
False
Can somebody provide me a minimal example with explanation of what is specialize doing, so I could freely use it?
Update
Trying to imitate how specialize works using apply I did the following:
Example specialize {A B: Type} (H: A -> B) (a: A): B.
Proof.
apply H in a.
This gives:
A : Type
B : Type
H : A -> B
a : B
============================
B
Almost the same as specialize, only different hypothesis name.
In test_nostutter_4 theorem I tried this and it worked:
remember (#eq_refl nat 1) as Heq.
apply H2 in Heq as H3.
It gives us:
H1 : 3 <> 1
H : nostutter [1; 4]
H2 : 1 = 1 -> False
Heq : 1 = 1
H3 : False
HeqHeq : Heq = eq_refl
============================
False
This one was more complex, we had to introduce a new hypothesis Heq. But we got what we need - H3 at the end.
Does specialize internally use something like remember? Or is it possible to solve it with apply but without remember?
specialize, in its simplest form, simply replaces a given hypothesis with that hypothesis applied to some other term.
In this proof,
Example specialize {A B: Type} (H: A -> B) (a: A): B.
Proof.
specialize (H a).
exact H.
Qed.
we initially have the hypothesis H: A -> B. When we call specialize (H a), we apply H to a (apply as in function application). This gives us something of type B. specialize then gets rid of the old H for us and replaces it with the result of the application. It gives the new hypothesis the same name: H.
In your case, we have H2: 1 = 1 -> False, which is a function from the type 1 = 1 to the type False. That means that H2 applied to eq_refl is of type False, i.e. H2 eq_refl: False. When we use the tactic specialize (H2 eq_refl)., the old H2 is cleared and replaced by a new term (H2 eq_refl) whose type is False. It keeps the old name H2, though.
specialize is useful when you're sure that you're only going to use a hypothesis once, since it automatically gets rid of the old hypothesis. One disadvantage is that the old name may not fit the meaning of the new hypothesis. However, in your case and in my example, H is a generic enough name that it works either way.
To your update...
specialize is a core tactic defined directly in the ltac plugin. It doesn't use any other tactic internally, since it is its internals.
If you want to keep a hypothesis, you can use the as modifier, which works for both specialize and apply. In the proof
Example specialize {A B: Type} (H: A -> B) (a: A): B.
Proof.
if you do specialize (H a) as H0., instead of clearing H, it'll introduce a new hypothesis H0: B. apply H in a as H0. has the same effect.

How to prove forall (p q:Prop), ~p->~((p ->q) ->p). using coq

I am completely new to coq programming and unable to prove below theorem. I need help on steps how to solve below construct?
Theorem PeirceContra: forall (p q:Prop), ~p->~((p ->q) ->p).
I tried the proof below way.
Given axiom as Axiom classic : forall P:Prop, P \/ ~ P.
Theorem PeirceContra: forall (p q:Prop), ~ p -> ~((p -> q) -> p).
Proof.
unfold not.
intros.
apply H.
destruct (classic p) as [ p_true | p_not_true].
- apply p_true.
- elimtype False. apply H.
Qed.
Getting subgoal after using elimtype and apply H as
1 subgoal
p, q : Prop
H : p -> False
H0 : (p -> q) -> p
p_not_true : ~ p
______________________________________(1/1)
p
But now I am stuck here because I am unable to prove P using p_not_true construct of given axiom......Please suggest some help......
I am not clear how to use the given axiom to prove logic................
This lemma can be proved constructively. If you think about what can be done at each step to make progress the lemma proves itself:
Lemma PeirceContra :
forall P Q, ~P -> ~((P -> Q) -> P).
Proof.
intros P Q np.
unfold "~".
intros pq_p.
apply np. (* this is pretty much the only thing we can do at this point *)
apply pq_p. (* this is almost inevitable too *)
(* the rest should be easy *)
(* Qed. *)

Rewrite hypothesis in Coq, keeping implication

I'm doing a Coq proof. I have P -> Q as a hypothesis, and (P -> Q) -> (~Q -> ~P) as a lemma. How can I transform the hypothesis into ~Q -> ~P?
When I try to apply it, I just spawn new subgoals, which isn't helpful.
Put another way, I wish to start with:
P : Prop
Q : Prop
H : P -> Q
and end up with
P : Prop
Q : Prop
H : ~Q -> ~P
given the lemma above - i.e. (P -> Q) -> (~Q -> ~P).
This is not as elegant as just an apply, but you can use pose proof (lemma _ _ H) as H0, where lemma is the name of your lemma. This will add another hypothesis with the correct type to the context, with the name H0.
This is one case where ssreflect views do help:
From Coq Require Import ssreflect.
Variable (P Q : Prop).
Axiom u : (P -> Q) -> (~Q -> ~P).
Lemma test (H : P -> Q) : False.
Proof. move/u in H. Abort.
apply u in H does also work, however it is too smart for its own good and does too much.
If I wanted to transform H in place I would go with #ejgallego's answer, since SSReflect is now (starting from Coq 8.7.0) a part of standard Coq, but here is another option:
Ltac dumb_apply_in f H := generalize (f H); clear H; intros H.
Tactic Notation "dumb" "apply" constr(f) "in" hyp(H) := dumb_apply_in f H.
A simple test:
Variable (P Q : Prop).
Axiom u : (P -> Q) -> (~Q -> ~P).
Lemma test (H : P -> Q) : False.
Proof. dumb apply u in H. Abort.

apply tactic cannot find an instance for a variable

I have been trying out apply tactic in various scenarios and it seems to stuck in the following case when premises are like this:
H1 : a
H2 : a -> forall e : nat, b -> g e
============================
...
When I try apply H2 in H1., it gives me the error:
Error: Unable to find an instance for the variable e.
Any way for me to bring forall e : nat, b -> g e as part of premises. This is the full working code with the above scenario:
Lemma test : forall {a b c : Prop} {g : nat} (f : nat -> Prop),
a /\ (a -> forall {e : nat}, b -> f e) -> c.
Proof.
intros a b c f g.
intros [H1 H2].
(* apply H2 in H1. *)
Abort.
The Coq Reference manual, ยง8.2.5:
The tactic apply term in ident tries to match the conclusion of the type of ident against a non-dependent premise of the type of term, trying them from right to left. If it succeeds, the statement of hypothesis ident is replaced by the conclusion of the type of term.
Now, applying the above description to your case, we get the following, Coq tries to replace H1 : a with the conclusion of H2, i.e. g e. To do that it needs to instantiate the universally quantified variable e with some value, which Coq cannot obviously infer -- hence the error message you've seen.
Another way to see that is to try a different variant of apply ... in ...:
eapply H2 in H1.
which will give you two subgoals:
...
H2 : a -> forall e : nat, b -> g e
H1 : g ?e
============================
c
and
...
H1 : a
H2 : a -> forall e : nat, b -> g e
============================
b
The H1 hypothesis of the first subgoal shows what Coq was going for with the ordinary apply in tactic, but in the eapply in case the variable e got replaced with an existential variable (?e). If you are not familiar with existential variables yet, then they are sort of promise you make to Coq that you'll build terms for them later. You are supposed to build the terms implicitly, via unification.
Anyways, specialize (H2 H1). might be what you want to do, or something like this
pose proof (H2 H1) as H; clear H1; rename H into H1.

apply argument to equal functions in Coq

Suppose I have two functions f and g and I know f = g. Is there a forward reasoning 'function application' tactic that will allow me to add f a = g a to the context for some a in their common domain? In this contrived example, I could use assert (f a = g a) followed by f_equal. But I want to do something like this in more complex situations; e.g.,
Lemma fapp : forall (A B : Type) (P Q : A -> B) (a : A),
(fun (a : A) => P a) = (fun (a : A) => Q a) ->
P a = Q a.
I think I can't correctly infer the general problem that you have, given your description and example.
If you already know H : f = g, you can use that to rewrite H wherever you want to show something about f and g, or just elim H to rewrite everything at once. You don't need to assert a helper theorem and if you do, you'll obviously need something like assert or pose proof.
If that equality is hidden underneath some eta-expansion, like in your example, remove that layer and then proceed as above. Here are two (out of many) possible ways of doing that:
intros A B P Q a H. assert (P = Q) as H0 by apply H. rewrite H0; reflexivity.
This solves your example proof by asserting the equality, then rewriting. Another possibility is to define eta reduction helpers (haven't found predefined ones) and using these. That will be more verbose, but might work in more complex cases.
If you define
Lemma eta_reduce : forall (A B : Type) (f : A -> B),
(fun x => f x) = f.
intros. reflexivity.
Defined.
Tactic Notation "eta" constr(f) "in" ident(H) :=
pattern (fun x => f x) in H;
rewrite -> eta_reduce in H.
you can do the following:
intros A B P Q a H. eta P in H. eta Q in H. rewrite H; reflexivity.
(That notation is a bit of a loose cannon and might rewrite in the wrong places. Don't rely on it and in case of anomalies do the pattern and rewrite manually.)
I don't have a lot of experience with Coq or its tactics, but why not just use an auxiliary theorem?
Theorem fapp': forall (t0 t1: Type) (f0 f1: t0 -> t1),
f0 = f1 -> forall (x0: t0), f0 x0 = f1 x0.
Proof.
intros.
rewrite H.
trivial.
Qed.
Lemma fapp : forall (A B : Type) (P Q : A -> B) (a : A),
(fun (a : A) => P a) = (fun (a : A) => Q a) ->
P a = Q a.
Proof.
intros.
apply fapp' with (x0 := a) in H.
trivial.
Qed.